التمثيل الخرائطي للخصائص المورفومترية لحوض وادي فؤاد جنوب غرب: بحيرة الرزازة باستخدام تقنيتي الاستشعار عن بعد ونظم المعلومات الجغرافية - الحميري، محمد عباس جابر (جامعة بغداد - كلية الآداب, 2019)
The present study aims to use the remote sensing data, GIS software, topographic and geological maps in the mapping process of the morphometric characteristics of Wadi Fuad basin. The study refers to the spatial characteristics, dimensions, morphological characteristics, surface characteristics, characteristics of the water drainage system, as well as the longitudinal, and natural factors. These techniques revealed that the area of the basin reached (259.22 km2), and its water goes to the Razzazah lake in the rainy season, and the basin divided into three secondary basins varied in their area according to the geomorphological factors and processes that contributed to its formation. The mathematical laws of the morphometric characteristics revealed that the basin is close to the rectangular shape. It is a very steep and zigzag triangle, and the valley passes through the beginning of maturity of its geomorphological stages. The total number of mattresses was six, including 1064 courses and a length of 731.07 km.
تهدف الدراسة الحالية إلى استخدام معطيات الاستشعار عن بعد وبرمجيات نظم المعلومات الجغرافية والخرائط الطبوغرافية والجيولوجية في عملية التمثيل الخرائطي للخصائص المورفومترية لحوض وادي فؤاد والتي تتمثل بالخصائص المساحية والأبعاد والخصائص الشكلية والتضاريسية وخصائص شبكة الصرف المائي فضلا عن المقاطع الطبوغرافية الطولية والعرضية والعوامل الطبيعية. وكشفت تلك التقنيات أن مساحة الحوض بلغت (259.22 كم2)، وتنصرف مياهه إلى بحيرة الرزازة في موسم تساقط الأمطار، وقسم الحوض على ثلاثة أحواض ثانوية تباينت في مساحاتها وفقا للعوامل والعمليات الجيومورفولوجية التي أسهمت في تكوينها. وقد كشفت القوانين الرياضية الخاصة بالخصائص المورفومترية أن الحوض يقترب من الشكل المستطيل، ويكون مثلث شديد التعرج، وأن الوادي يمر ببداية مرحلة النضج من مراحله الجيومورفولوجية، وبلغت مجموع المراتب فيه ست مراتب، تضمنت (1064) مجرى، وبطول (731.07 كم).
Keywords: التمثيل الخرائطي -- الاستشعار عن بعد -- نظم المعلومات الجغرافية -- بحيرة الرزازة -- حوض وادي فؤاد